PENGOLAHAN DAN ANALISIS DATA LEBIH BAYAR DAN KURANG BAYAR DANA BAGI HASIL SUMBER DAYA ALAM (LK BA-BUN 999.05 TA 2012-2016) - Deni Herdiyana, SE., MM., M.Acc. Fin. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
This study aims to find out whether recognition, recording, summarizing and reporting of receivables (LB) and obligations (KB) Sharing Revenue Fund - Natural Resources (DBH SDA) is in accordance with the applicable source documents and Government Accounting Standards (SAP) through a descriptive analysis approach. The results of the study can be concluded that there is a transition period on the basis of accounting in recording LB and KB DBH SDA, namely the transition from the Cash Toward Accrual (CTA) basis to the Accrual basis. And also there is a transfer of accounting principles in the recognition and recording of LB and KB DBH SDA, namely from the principle of substance over form to the principle of formality. In addition, it is known that the payment period for LB DBH SDA is faster than payment for KB DBH SDA.